Laparoscopy and Laparotomy for Endometrioid Adenocarcinoma: Short- and Long-Term Outcomes’ Comparison - Lan Hong; Xiuzhen Wang; Shengtan Wang; Wei Li; Lang Zheng; Jun Liu; Haocheng Gao; Xiaohang Liu; Guifei Li; Lifan Shen; Hengzhi Zhuang; Genhai Zhu (International Journal of Clinical Practice)
Aims. To analyze the short-term and long-term outcomes of laparoscopy versus laparotomy in treatment of endometrioid adenocarcinoma and examine the benefits of laparoscopy. Methods. From January 2012 to July 2020, 693 endometrioid adenocarcinoma patients undergoing laparoscopy versus laparotomy were retrospectively identified and enrolled in this study. Basic information for the patients, their perioperative indexes, and recurrence rates were reviewed to assess the therapeutic effect of these two approaches for endometrioid adenocarcinoma. Results. A total of 365 endometrioid adenocarcinoma patients underwent laparoscopy, and 328 patients underwent laparotomy. When compared with the laparotomic group, the laparoscopic group had longer operative times, lower intraoperative bleeding volumes, and shorter postoperative hospital stays. The rate of less-radical hysterectomy and radical hysterectomy performed in the laparoscopic group (59/365, 16.16%) was significantly lower than that in the laparotomic group (162/328, 49.39%). There was no statistically significant difference in the local recurrence rate between the two groups; however, the remote recurrence rate in the laparotomic group (15/308, 4.87%) was significantly higher than that in the laparoscopic group (3/351, 0.85%). A further subgroup analysis revealed a higher survival benefit both in I/II patients (314/314, 100%, vs. 7/242, 28.93%) and III/IV patients (35/37, 94.59%, vs. 51/66, 77.27%) in the laparoscopic group, when compared with the laparotomic group. Conclusion. Patients who received laparoscopic surgery had a faster surgical recovery and a lower postoperative recurrence rate in the short term than patients who received laparotomic surgery. Laparoscopic surgery is a safe and effective treatment for endometrioid adenocarcinoma.